Study of Laser Raman Spectra of 2-Pyridyl Methyl Thiourea - Natarajan, A.; Pragasam, S. (Asian Journal of Chemistry, 2010)
Laser Raman spectra of 2-pyridyl methyl thiourea has been recorded. The characteristic vibrational frequencies of the pyridyl and NH groups and the aromatic rings have been identified by correlating the assignments with those available for related systems.